PHYTOCHEMICAL SCREENING, ANTI-INFLAMMATORY AND ANALGESIC PROPERTIES OF PENTANISIA PRUNELLOIDES FROM THE EASTERN CAPE PROVINCE, SOUTH AFRICA - Mathews, Miya Gugulethu; Ajayi, Oyemitana, Idris; Opeoluwa, Oyedeji Oyehan; Oluwatobi, Oluwafemi Samuel; Benedicta, Nkeh-Chungag N; Phindile, Songca Sandile; Omowumi, Oyedejia Adebola (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background Pentanisia prunelloides is a medicinal plant widely used to remedy various ailments including infections, fever andrheumatism in Eastern Cape Province of South Africa. There is scanty report on the phytochemical and biological properties of theplant; hence various solvent extracts of the dried plant materials were phytochemically screened, and its aqueous extract evaluated foracute toxicity effect, analgesic and antiinflammatory properties in rodents.Methods and Materials: Different extracts of both leaf and rhizome were obtained separately with ethanol, methanol and water.Portions of the filtrate were used for qualitative screening of secondary metabolites and remaining portions were concentrated anddried. Dried grounded leaf and rhizome of the plant were also used for quantitative screening for some major components. The aqueousextract of the leaf and rhizome were used for acute toxicity (LD50) test, antiinflammatory and analgesic activities in rodents.Results: The qualitative phytochemical screening showed the presence of several phytoconstituents with saponins, flavonoids andalkaloids constituting highest constituents in the leaf and rhizome. The LD50 of the aqueous extracts (from leaf or rhizome) was foundto be ≥5000 mg/kg orally. The leaf and rhizome aqueous extract (250-500 mg/kg) significantly (p<0.01) reduced egg albumin-inducedpaw oedema and paw licking in mice induced by formalin, signifying antinociceptive and antiinflammatory activities respectively.Conclusion It is concluded that the leaf and rhizome of P. prunelloides are rich in various phytochemicals which could be associatedwith their medicinal uses. The aqueous leaf and rhizome extracts are similarly non-toxic orally, showed antiinflammatory and analgesicpotentials thus rationalizing its use in folkloric medicine.